1989
DOI: 10.1161/01.str.20.8.1065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraluminally versus extraluminally administered nimodipine on serotonin-induced cerebral vascular responses in vitro and in situ.

Abstract: The purpose of our study was to compare the ability of intraluminally and extraluminally administered nimodipine to inhibit serotonin-induced cerebral vascular responses in vitro and in situ. No difference was noted in the ability of nimodipine, whether administered intraluminally or extraluminally, to reduce the contractile response of extraluminally administered serotonin in a closed, pressurized, in vitro bovine middle cerebral artery preparation; histologic studies indicated that the tight endothelial junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…One to two centimeters of whole, straight sections of artery were cannulated between glass tubes and stretched lon gitudinally to their approximate in situ length (as measured before removal from the brain). Little damage was done to the endo thelium as suggested by previous studies [15], At 75 mm Hg intraluminal pressure, the outer diameter (OD) ranged from 1.4 to 1.8 mm. Maximum contractions with 5-HT are obtained at this intraluminal pressure [14], The arteries were perfused intraluminally with n-Krebs solution by means of a peristaltic pump (Harvard Apparatus), while the pressure was monitored with Statham pressure transducers.…”
mentioning
confidence: 99%
“…One to two centimeters of whole, straight sections of artery were cannulated between glass tubes and stretched lon gitudinally to their approximate in situ length (as measured before removal from the brain). Little damage was done to the endo thelium as suggested by previous studies [15], At 75 mm Hg intraluminal pressure, the outer diameter (OD) ranged from 1.4 to 1.8 mm. Maximum contractions with 5-HT are obtained at this intraluminal pressure [14], The arteries were perfused intraluminally with n-Krebs solution by means of a peristaltic pump (Harvard Apparatus), while the pressure was monitored with Statham pressure transducers.…”
mentioning
confidence: 99%
“…Previous studies indicate that a 5-mg dose of 5-HT (though far above what is normally found in the CSF of humans or animals) was necessary to produce significant decreases in angiographically measured vessel diameter (28). It may be argued that we did not determine how much 5-HT was actually reaching the point of impact, the circle of Willis; thus, our variability may be due to drug-concentration differences at the base of the brain.…”
Section: Discussionmentioning
confidence: 80%